Perception, knowledge and awareness towards the attitude on organ donation among staffs of UiTM Cawangan Kelantan / Annur Liyana Mohd Kemari, Nur Ain Hidayah Zainuddin and Nurul Farhana Mohd Asri - Mohd Kemari, Annur Liyana; Zainuddin, Nur Ain Hidayah; Mohd Asri, Nurul Farhana (2019)
Organ donation is an act of people give or transplant their organs sincerely and not based on monetary value. However, the previous studies show that Malaysia is one of the countries which has a lower rate of organ and tissue donation compared to other countries in the world. Based on previous studies, negative perception, poor knowledge and lack of awareness are the reasons for the problem occurred. Hence, this study focuses on identifying the significant and direct effect of perception, knowledge and awareness towards the attitude on organ donation. Not only that, this study identifies the significant difference in mean of attitude between different levels of demographic factors involving gender, marital status, income and highest educational level. This study applied a cross-sectional study on 249 staffs consisting academic and non-academic staffs in UiTM Cawangan Kelantan and the sample were chosen by using Simple Random Sampling. This study recorded 100.00% of response rate. In order to collect the data, self-administered questionnaire was used. The statistical analysis that have been applied to achieve the objectives were Structural Equation Modelling (SEM), Independent t-test and Analysis of Variance (ANOVA) which both were analysed by using Statistical Package for Social Science (SPSS) version 21 and AMOS version 23 respectively. In conclusion, only perception has a significant and direct effect towards the attitude on organ donation. However, knowledge and awareness showed no significant and direct effect towards the attitude on organ donation. This study also concluded that there is no significant difference in mean of attitude between gender. Not only that, this study also found that there was a significant difference in mean of attitude between levels of income while the other variables (marital status, highest educational level) do not show any significant difference in mean of attitude among different levels. This study suggested some modifications such as conducting the study on large population and include new variables that may has possibility affect the attitude towards organ donation for further studies. This study also suggested several ways to build positive perception thus increase positive attitude by doing campaign, teach and encourage children about organ donation and give talk on the importance of donating organ